Flowering after disaster: Early Danian buckthorn (Rhamnaceae) - Jud, Nathan A. (2017)
Southern-Hemisphere terrestrial communities from the early Paleocene are poorly known, but recent work on Danian plant fossils from the Salamanca Formation in Chubut Province, Argentina are providing critical data on earliest Paleocene floras. The fossils described here come from a site in the Salamanca Formation dating to ca. 1 million years or less after the end-Cretaceous extinction event; they are the first fossil flowers reported from the Danian of South America, and possible the entire Southern Hemisphere. They are compressions and impressions in flat-laminated light gray shale, and they belong to the family Rhamnaceae (buckthorns). Flowers of Notiantha grandensis gen. et sp. nov. are pentamerous, with distinctly keeled calyx lobes projecting from the hypanthium, clawed and cucullate emarginate petals, antepetalous stamens, and a pentagonal floral disk that fills the hypanthium. Their phylogenetic position was evaluated using a molecular scaffold approach combined with morphological data. Results indicate that the flowers are most like those of extant ziziphoid Rhamnaceae. The associated leaves, assigned to Suessenia grandensis gen. et sp. nov. are simple and ovate, with serrate margins and three acrodromous basal veins. They conform to the distinctive leaves of some extant Rhamnaceae in the ziziphoid and ampelozizyphoid clades. These fossils provide the first unequivocal megafossil evidence of Rhamnaceae in the Southern Hemisphere, demonstrating that Rhamnaceae expanded beyond the tropics by the earliest Paleocene. Given previous reports of rhamnaceous pollen in the late Paleogene and Neogene of Antarctica and southern Australia, this new occurrence increases the possibility of high-latitude dispersal of this family between South America and Australia via Antarctica during the Cenozoic.